Penanaman Pendidikan Karakter Kepada Siswa Melalui Program Kurangi Sampah Sekolah Kita “Kurasaki” - Muhammad Dafa Dafiatur Rizqi; Pedro Yehezkiel; Reza Mauldy Raharja (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to investigate the effect of instilling character education through our school's waste reduction program